Impaired rRNA synthesis triggers homeostatic responses in hippocampal neurons - Kiryk, Anna; Kreiner, Grzegorz; Sowodniok, Katharina; Rodriguez-Parkitna, Jan; Sönmez, Aynur; Górkiewicz, Tomasz; Bierhoff, Holger; Wawrzyniak, Marcin; Janusz, Artur K.; Liss, Birgit; Konopka, Witold; Schütz, Günther; et al. (Frontiers in cellular neuroscience, 2013)
Decreased rRNA synthesis and nucleolar disruption, known as nucleolar stress, are primary signs of cellular stress associated with aging and neurodegenerative disorders. Silencing of rDNA occurs during early stages of Alzheimer´s disease (AD) and may play a role in dementia. Moreover aberrant regulation of the protein synthesis machinery is present in the brain of suicide victims and implicates the epigenetic modulation of rRNA. Recently, we developed unique mouse models characterized by nucleolar stress in neurons. We inhibited RNA polymerase I by genetic ablation of the basal transcription factor TIF-IA in adult hippocampal neurons. Nucleolar stress resulted in progressive neurodegeneration, although with a differential vulnerability within the CA1, CA3 and dentate gyrus. Here, we investigate the consequences of nucleolar stress on learning and memory. The mutant mice show normal performance in the Morris water maze and in other behavioral tests, suggesting the activation of adaptive mechanisms. In fact, we observe a significantly enhanced learning and re-learning corresponding to the initial inhibition of rRNA transcription. This phenomenon is accompanied by aberrant synaptic plasticity. By the analysis of nucleolar function and integrity, we find that the synthesis of rRNA is later restored. Gene expression profiling shows that thirty-six transcripts are differentially expressed in comparison to the control group in absence of neurodegeneration. Additionally, we observe a significant enrichment of the putative serum response factor (SRF) binding sites in the promoters of the genes with changed expression, indicating potential adaptive mechanisms mediated by the mitogen-activated protein kinase pathway. In the dentate gyrus a neurogenetic response might compensate the initial molecular deficits. These results underscore the role of nucleolar stress in neuronal homeostasis and open a new ground for therapeutic strategies aiming at preserving neuronal function.
Gesehen am 22.06.2022